Bangladesh Agricultural Value Chain (AVC) Impact Evaluation: Endline Survey - International Food Policy Research Institute (International Food Policy Research Institute, 2020)
Funded under the Feed the Future (FTF) Initiative, the Bangladesh Agricultural Value Chains (AVC) project was implemented by Development Alternatives International (DAI) and strove to improve food and nutrition security through strengthened agricultural value chains. This dataset contains data from the final round of household survey interviews from the Impact Evaluation associated with the Bangladesh AVC project, which covered producer and input retailer households for two value chains. The sample is divided into five groups. Groups 1 through 3 refer to interviews along the jute value chain, while groups 4 and 5 refer to interviews along the mung bean value chain. Group 1 households are jute farmer households interviewed in 2016, 2017 and 2018. Group 2 households are jute farmer households interviewed in 2017 and 2018 (after expanding the original sample). Group 3 households are jute input retailers interviewed in 2017 and 2018. Group 4 households are mung bean farmer households interviewed in 2018. Group 5 households are mung bean input retailers interviewed in 2018. Households completed two interview forms. A household-level form was administered to all households and included questions on household characteristics, agricultural production, and input purchases (or sales). An individual-level form was administered to male and female respondents, and included questions on household demographics and consumption. Group 2 households also completed a series of modules as part of the Project-Level Women’s Empowerment in Agriculture Index (Pro-WEAI).